2023
DOI: 10.3390/diagnostics13061194
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Neutralizing Antibodies in Mexican Population: A Five Vaccine Comparison

Abstract: Neutralizing antibodies (NAs) are key immunological markers and are part of the humoral response of the adaptive immune system. NA assays determine the presence of functional antibodies to prevent SARS-CoV-2 infection. We performed a real-world evidence study to detect NAs that confer protection against SARS-CoV-2 after the application of five vaccines (Pfizer/BioNTech, AstraZeneca, Sinovac, Moderna, and CanSino) in the Mexican population. Side effects of COVID-19 vaccines and clinical and demographic factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Notably, none of the three studies reported a significant difference in the antibody response rates of males and females [23]. However, in a study conducted with Mexican subjects, gender and differences in the percentage of neutralizing antibodies against the SARS-CoV-2 were found: Females had a higher percentage of antibody levels than males [24], which is in agreement with the present findings.…”
Section: Discussionsupporting
confidence: 89%
“…Notably, none of the three studies reported a significant difference in the antibody response rates of males and females [23]. However, in a study conducted with Mexican subjects, gender and differences in the percentage of neutralizing antibodies against the SARS-CoV-2 were found: Females had a higher percentage of antibody levels than males [24], which is in agreement with the present findings.…”
Section: Discussionsupporting
confidence: 89%
“…When comparing different types of vaccines, it becomes evident that Ad5-nCoV exhibits lower efficacy than mRNA vaccines. Nevertheless, it demonstrates a higher effectiveness in generating neutralizing antibodies when compared to other viral vector vaccines, such as the Ad26.COV2.S/Janssen [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, there are no studies that demonstrate the impact of the type of vaccine on placental transfer; however, a study carried out in the general population indicated that vaccination with Pfizer and Moderna has the best neutralization rates when compared with the AstraZeneca, Sinovac, and CanSino vaccines [29].…”
Section: Discussionmentioning
confidence: 99%